Mitigating plant environmental stressors: Exploring sustainable and eco-friendly solutions - Okon, Okon Godwin (Journal of Plant Stress Physiology, 2025)
Environmental stressors, both abiotic (e.g., drought, salinity, temperature extremes) and biotic (e.g., pests, diseases, weeds), pose significant challenges to plant health, affecting growth, yield, and overall agricultural productivity. Traditional mitigation methods, including chemical interventions and mechanical techniques, often come with environmental and sustainability concerns, necessitating a shift towards more sustainable practices. This review explores innovative approaches and technologies aimed at mitigating plant environmental stressors in an eco-friendly manner. Precision agriculture and smart farming, leveraging advanced technologies such as IoT, AI, and remote sensing, allow for optimized input application, enhancing crop resilience while minimizing environmental impact. The use of biostimulants and biofertilizers promotes plant growth and stress tolerance through natural mechanisms, reducing reliance on chemical fertilizers. Additionally, renewable energy and water conservation techniques, including solar-powered irrigation and rainwater harvesting, offer sustainable solutions to resource management in agriculture. The integration of these strategies, along with advancements in biotechnology such as genetic engineering and the development of stress-resistant crop varieties, provides a holistic approach to addressing the challenges posed by environmental stressors. As agriculture faces the dual pressures of increasing food demand and climate change, these innovative methods are crucial for ensuring sustainable crop production and long-term ecosystem health. The review highlights the need for continued research and ethical considerations in the adoption of these technologies to balance productivity with environmental stewardship.